510 Giant left atrial appendage aneurysm in a 47 years old male: a case report. (8th December 2021) - Coraducci, Francesca; Belleggia, Sara; Torselletti, Lorenzo; Coretti, Francesca; Valeri, Yari; Maiorino, Francesco; Ciliberti, Giuseppe; Barbarossa, Alessandro; Compagnucci, Paolo; Stronati, Giulia; Casella, Michela; Russo, Antonio Dello; et al.
Abstract: Aims: Left atrial appendage aneurysm (LAAA) is a rare condition mostly due to congenital malformations or secondary causes. Methods and results: Since very few cases are described in the literature, there is uncertainty in treatment and prognosis. Diagnosis is achieved by advanced imaging as transesophageal echocardiography (TEE), which also allows the detection of thrombus, moreover cardiac magnetic resonance (CMR) could be more specific in describing sizes and relationships with surrounding anatomical structures. Surgical aneurysmectomy could be indicated in the majority of cases, especially if compression of other cardiac chambers or mediastinal structures are present. Medical therapy can include tromboprophylaxys and arrhythmias management. Since high quality evidence is scarce, a shared decision making by Heart Team approach should be considered. We present the case of a 47 years old male who came to our attention for palpitations and epigastric pain. The ECG showed high ventricular rate atrial fibrillation (AF) with wide QRS (left bundle branch block morphology). Due to haemodynamic instability the patient underwent urgent electrical cardioversion and coronary angiography showed patent coronary arteries. He had a giant left auricle appendage diagnosed twelve years before and was on antiarrhythmic prophylaxis for previous AF episodes. A TEE was performed and confirmed the diagnosis of LAAA also showing hypokinetic anterior-apical wall due to the interplay with the giant aneurysm. Subsequent CMR showed no LGE and confirmed the absence of thrombus in the LAAA. After Heart Team consultation surgical treatment was proposed to the patient who refused any invasive procedure. Therefore medical treatment was achieved by direct oral anticoagulation and antiarrhythmic therapy with betablockers and flecainide per os. Moreover, a loop recorder for longitudinal monitoring was implanted. At 6 months of follow-up the patient was asymptomatic except for a brief paroxysm of self-limited AF.